The role of agricultural insurance in the prevention of financing risks in the form of slam : "An Empirical Study on Shikan Insurance and Reinsurance Company (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The aim of this research is to introduce agricultural insurance, to define financing in the form of salam and the role of agricultural insurance in the prevention of risks to agricultural finance operations in the form of salam by verifying the hypotheses through which to reach the results, including the imposition of risks for agricultural finance in the form of salam, The study of agricultural finance in the form of salm, the deductive approach to the development of the problem of research and hypotheses, and the inductive method to extrapolate the results through analysis and brother The researcher concluded that agricultural insurance works to bridge the risks facing agricultural finance in the form of the ladder in cases of negligence or lack by the client or cases in which the client does not have a hand in terms of natural disasters Floods, etc. The insurance may also cause damage to its ability only in cases of minor damage or increase by the total value greater than half, and the researcher is recommended to pay attention to agricultural insurance on the financing in the form of peace and the holding of workshops and seminars in the field of insurance and finance Form husband.